SIRT2 Promotes HBV Transcription and Replication by Targeting Transcription Factor p53 to Increase the Activities of HBV Enhancers and Promoters - Wu, Dai-Qing; Ding, Qiu-Ying; Tao, Na-Na; Tan, Ming; Zhang, Yuan; Li, Fan; Zhou, Yu-Jiao; Dong, Mei-Ling; Cheng, Sheng-Tao; Ren, Fang; Chen, Juan; Ren, Ji-Hua (Frontiers in Microbiology, 2022)
Chronic hepatitis B virus infection is one of the leading causes of cirrhosis and liver cancer. Although the major drugs against Chronic Hepatitis B including nucleos(t)ide analogs and PEG-interferon can effectively control HBV infection, complete cure of HBV infection is quite rare. Targeting host factors involved in the viral life cycle contributes to developing innovative therapeutic strategies to improve HBV clearance. In this study, we found that the mRNA and protein levels of SIRT2, a class III histone deacetylase, were significantly upregulated in CHB patients, and that SIRT2 protein level was positively correlated with HBV viral load, HBsAg/HBeAg levels, HBcrAg and ALT/AST levels. Functional analysis confirmed that ectopic SIRT2 overexpression markedly increased total HBV RNAs, 3.5-kb RNA and HBV core DNA in HBV-infected HepG2-Na+/taurocholate cotransporting polypeptide cells and primary human hepatocytes. In contrast, SIRT2 silencing inhibited HBV transcription and replication. In addition, we found a positive correlation between SIRT2 expression and HBV RNAs synthesis as well as HBV covalently closed circular DNA transcriptional activity. A mechanistic study suggested that SIRT2 enhances the activities of HBV enhancer Ⅰ/ HBx promoter (EnⅠ/Xp) and enhancer Ⅱ/HBc promoter (EnⅡ/Cp) by targeting the transcription factor p53. The levels of HBV EnⅠ/Xp and EnⅡ/Cp-bound p53 were modulated by SIRT2. Both mutation of p53 binding sites in EnⅠ/Xp and EnⅡ/Cp as well as overexpression of p53 abolished the effect of SIRT2 on HBV transcription and replication. In conclusion, our study reveals that, in terms of host factors, a SIRT2-targeted program might be a more effective therapeutic strategy for HBV infection.